Zakon SS. Sióstr Zgromadzenia Dzieci Marii opieki św. Józefa obrządku bizantyjsko-słowiańskiego na terenie diecezji gorzowskiej w latach 1952-1962 = The order of SS. in the Congregation of Mary's Children under the custody of St. Joseph in Byzantine-Slavonic Rite in Gorzów's bishopic in the years 1952-1962 - Woźniak, Sylwester (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
It is common knowledge that Catholic Church in Poland operates in a number of rites. One ofthem is the Byzantine-Slavonic Rite, often called neounion. In historiography dealing with thequestion a number of works has been devoted to the issue of the creation and the development of the rite in the eastern area of the Second Republic of Poland. At present, there operates one parish in the rite. It is located in Kostomloty, lubelskie voivodship.
Keywords: Zakon SS. Sióstr Zgromadzenia Dzieci Marii opieki św. Józefa obrządku bizantyjsko-słowiańskiego; kościół katolicki - obrządek bizantyjsko-słowiański; neounia; zakony - 20 w.; diecezja gorzowska